The Relationship of Adolescent Self-Control with Covid-19 Health Protocol Adherence (Survey of Adolescents in Palembang City) - Pratama, Erfandi; Nur Alam Fajar; Nurmala, Ira Nurmala; Mochammad Bagus Qomaruddin; Kaima Ishmata Rianti (Universitas Airlangga, 2023)
Background: COVID-19 is a health problem that is currently a global concern caused by SARS-CoV-2 infection. South Sumatra Province has a percentage of COVID-19 mortality rate of 5.92%, which exceeds the national mortality percentage of 4.1%. Elimination of COVID-19 cases is one of the implementations of the Sustainable Development Goals (SDGs) which aims to end the epidemic of infectious diseases by 2030. Adolescents are faced with the ability to control their attitudes well in order to be consistent in action and achieve emotional maturity and character building. Objectives: to analyze the relationship between adolescent self-control and compliance with COVID-19 health protocols. Methods: This research uses the analytical observational method with a quantitative approach with a cross-sectional design. This study's respondents were 100 samples using the voluntary sampling method. Information was collected online via Google form in February 2021. Data were analyzed using a simple linear regression test. Results: Univariate results showed that compliance with the COVID-19 health protocol was 53%. There was a significant relationship between behavioral, cognitive, and decision control on compliance with the COVID-19 health protocol. Linear regression results show a moderate and positive relationship between behavioral control (r = 0.274), cognitive control (r = 0.425), and decision control (r = 0, 473) to compliance with COVID-19 health protocols. Conclusions: Adolescents in Palembang City have good self-control so that they can modify and control behavior, manage information, and choose actions on COVID-19 protocols.